Study of the distribution of journals across subject categories and the method of evaluation for papers of different subject categories in SCI - FANH Yong-cai; WU Guang-hao; CHEN Lei (浙江大学学报. 农业与生命科学版, 2004)
Using data in the 2002 edition of the ISI “Journal Citation Reports”. the distribution of journals across subject categories and the various indices of journals in different subject categories were summarized statistically. The results indicate an uneven distribution of the number of journals as well as the most frequently cited journals across subject categories. Methods are suggested for the evaluation of papers published in journals of different subject categories, and using the papers published by two research teams from Zhejiang University a comparative evaluation was attempted to demonstrate the significance of the proposed methods.